Adolescent Physical Activity: Role of School Support, Role Models, and Social Participation in Racial and Income Disparities. (January 2016) - Babey, Susan H.; Wolstein, Joelle; Diamant, Allison L.
Few youth meet current physical activity recommendations. Protective social factors such as having a role model, social participation, and adult support at school may help promote youth physical activity. This study used data from the 2011-2012 California Health Interview Survey to examine the extent to which role models, social participation, and support at school promote physical activity among groups at risk of inactivity and obesity, specifically low-income youth and youth of color. In a model including all adolescents, those who participated in organizations outside school, did volunteer work, reported higher support from adults at school, and reported having an athlete as a role model were more physically active. However, associations varied by gender, income, and race/ethnicity. These findings suggest that some of these protective social factors, especially school support, may help promote physical activity among Latino, African American, and low-income youth, groups at increased risk of physical inactivity.